2012
DOI: 10.7307/ptt.v23i1.144
|View full text |Cite
|
Sign up to set email alerts
|

A Data Mining Approach to Identify Key Factors of Traffic Injury Severity

Abstract: Seventy percent of the traffic crash fatalities of Iran happen on rural roads, and a significant proportion of the rural roads network of this country is constituted of the main twolane, two-way roads. The purpose of this study is to identify the most important factors which affect injury severity of drivers involved in traffic crashes on these roads, so that by eliminating or controlling such factors an overall safety improvement can be accomplished. Using the Classification and Regression Tree (CART), one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These criteria were based on an analysis of the distributions of the samples of the four original driver-injury classes, among which there is an important imbalance of data (there are few dead drivers compared to the number of minor or unharmed drivers). As other authors point out [27,31,39], it is more efficient to work with balanced data, which is the approach that has been adopted in this work.…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…These criteria were based on an analysis of the distributions of the samples of the four original driver-injury classes, among which there is an important imbalance of data (there are few dead drivers compared to the number of minor or unharmed drivers). As other authors point out [27,31,39], it is more efficient to work with balanced data, which is the approach that has been adopted in this work.…”
Section: Data Descriptionmentioning
confidence: 99%
“…To reduce type-1 errors considering cross validation, the dataset was split randomly into two parts: a training set (70% of the data) and a testing set (the remaining 30%), as done in previous works [31,39].…”
Section: Classification Tree Model (Cart)mentioning
confidence: 99%
“…Depaire et al [13] used clustering technique to analyze road accident data of Belgium and suggest that cluster-based analysis of road accident data can extract better information rather analyzing data without clustering. Kashani et al [14] used classification and regression tree (CART) to analyze road accidents data of Iran and found that not using seat belt, improper overtaking and speeding badly affect the severity of accidents. Kwon et al [15] used Naïve Bayes and decision tree classification algorithm to analyze factor dependencies related to road safety.…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantage of the parameter model-based method, such as regression analysis, is that the predefined underlying relationships between different variables could produce an erroneous estimation of the accident likelihood. The classification and regression tree (CART) is a powerful tool used for factor classification and ranking by importance [13]. It has been widely used in the crash mechanism and accident frequency analysis, traffic flow estimation and injury severity estimation [14][15][16].…”
Section: Dynamic Bayesian Network-based Escape Probability Estimation For Coach Fire Accidentsmentioning
confidence: 99%